Studi Struktur Mikro dan Kuat Lentur Komposit Geopolimer Serat Bambu dengan Temperatur Curing Berbeda: Vicran Zharvan, Muris, Subaer - Vicran Zharvan, Vicran Zharvan; Muris, Muris; Subaer, Subaer (Jurnal Fisika dan Aplikasinya, 2025)
Microstructure and flexural strength of composite-geopolymers based on metakaolin with bamboo fibers aggregate have been studied.The main objective of this study was to determine the flexural strength of composite geopolymers as a function of bamboo fibers mass (0.4 g, 0.6 g, and 0.8 g) as well as their curing temperatures (150, 450, dan 7500 C). Composite-geopolymers were synthesized by using alkali activation method of metakaolin and they were formed in rectangular sandwich shape by varying the mass of bamboo fibers and then cured at 600 C for 1 hour. The sample was then recurring at temperature of 150, 450, dah 7500 C, respectively. The morphology of the precursors and samples were examined by using SEM and XRD. Thermal properties of bamboo fibers were studied by using differential Perkin Elemer 400 differential scanning calorimetry (DSC). SEM characterization shows that the bond between the matrix of geopolymer and the aggregate is still weak due to the presence of appreciable wide gap. The matrix of geopolymer was amorf in nature based on XRD result. Three bending points flexural strength measurements on three samples for each composition and curing temperature showed that the highest flexural strength was achieved on fiber addition of 0.6 g (1.5% of sample volume) for all curing temperatures with magnitude of 665.90 ± 98.40 KPa, 947.29 ± 287.13 KPa dan 1155.62 ± 98.30 KPa.